(untitled) (Fiep Bulletin - online, 2014)
The objective of this study was to compare the effects of aerobic and resistance training in the maximum oxygen consumption in practitioners from a gym. The sample was composed by 8 subjects, of both genders, from 18 to 22 years old. The subjects were divided into 2 groups and, afterwards, participated on 2 training programs: aerobic and resistance. Maximum oxygen uptake and anthropometric data were collected in the beginning and end of the first and second training programs. There was an interval of 4 weeks between the two training programs, consisting of 4 weeks of rest without any physical activity. Both programs presented improvement of VO2max . Aerobic training VO2max increase was 15.5%, and resistance training VO2max increase was 7.8%. Although resistance training presented a smaller increase in VO2max , it has been a motivating exercise alternative due to its variety of movements and load, which establishes new routines or the practitioners. On the other hand, aerobic training is sometimes monotonous by the location of equipments and its routine.